Preparation of Aluminum Borate (Al4B2O9) Nanowires by Borax - Wang, Guosheng; Guo, Lianhao; Wang, Yingming (Asian Journal of Chemistry, 2014)
Aluminum nitrate [Al(NO3)3·9H2O] and sodium borate [Na2B4O7·10H2O] powders were used as starting materials, chiral (L- or D-) tartaric acid was added to serve as dispersing agent, a sol-gel process followed by annealing was employed to fabricate single crystal aluminum borate (Al4B2O9) nanowires. the S-types curve of pH value of the solution system under certain ratio of Al/B was to be nominated and to be promising in a large-scale production of aluminum borate (Al4B2O9) nanowires.